2011
DOI: 10.1134/s1054660x12020314
|View full text |Cite
|
Sign up to set email alerts
|

Diode-pumped continuous-wave Nd3+:YAlO3 intracavity-doubled red laser

Abstract: It is reported that efficient continuous wave (CW) red laser generation at 670 nm in a LBO crystal at type I phase matching direction performed with a diode pumped Nd 3+ :YAlO 3 (Nd:YAP) laser. With inci dent pump power of 15.6 W, output power of 273 mW at 670 nm has been obtained using a 10 mm long LBO crystal. At the output power level of 273 mW, the output stability is better than 3.7%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Intra-cavity frequency conversion has the advantage of low threshold, compact structure and high conversion efficiency, because this structure can improve the intensity density of fundamental and harmonic wave radiation in the nonlinear crystal. The intra-cavity frequency conversion method has been used for generating some wavelength like 670 nm [10], 532 nm [11], 355 nm [12], 305 nm [13] and so on. With regard to 355 nm laser, in 1999, Roiss et al reported 355 nm picosecond pulses of 10 ps duration with 0.5 mW average power at 150 MHz repetition rate [14].…”
Section: Laser Physics Lettersmentioning
confidence: 99%
“…Intra-cavity frequency conversion has the advantage of low threshold, compact structure and high conversion efficiency, because this structure can improve the intensity density of fundamental and harmonic wave radiation in the nonlinear crystal. The intra-cavity frequency conversion method has been used for generating some wavelength like 670 nm [10], 532 nm [11], 355 nm [12], 305 nm [13] and so on. With regard to 355 nm laser, in 1999, Roiss et al reported 355 nm picosecond pulses of 10 ps duration with 0.5 mW average power at 150 MHz repetition rate [14].…”
Section: Laser Physics Lettersmentioning
confidence: 99%